Peranan Nilai Philosofi Bugis Terhadap Proses Pengislaman Kerajaan Bugis Makassar di Sulawesi Selatan - Patmawati Patmawati (Khatulistiwa, 2016)
The Bugis philosophical values about monotheism, i.e. God almighty, come from ephos Galigo, namely Dewataseuae (the Only God), Datu Palanro (the Creator), Aji Patoto (the Law Giver), La Puang e (the Owner), he is the first, who provides grace and punishes the guilty. These values are in line with the values of monotheism in Islam. Islam entered South Sulawesi in the early seventeenth century brought by three Datoks: Datok ri Bandang, Datok ri Tiro and Datok ri Patimang. These three ulemas spread Islam in the palace. Therefore, the growth of Islam in South Sulawesi never had a clash between religions (sara') and the ruler (royaltycustoms). Customary people (nobility) and the religious (sara') supported each other in the spread of Islam. Once Islam had been accepted, the Bugis philosophy namely pangngaderreng/ pangngadakkang which consists of ade', wari, rapang, talk) was finally added with sara' as one of the elements of pangngaderreng / pangngadakkang.